2015
DOI: 10.15406/ogij.2015.02.00054
|View full text |Cite
|
Sign up to set email alerts
|

Intracervical Foley Catheter versus Vaginal Prostaglandins for Induction of Labor in Women with Previous One Cesarean Section-A Pilot Study

Abstract: Objective: To compare the efficacy, safety and acceptability of Intracervical foley catheter, dinoprostone and misoprostol, for induction of labor in women with previous one cesarean section at term. Study design:A prospective quasi-randomised clinical trial included 90 term pregnant women who were randomly assigned to receive intracervical foley catheter, dinoprostone 3 mg tablets or misoprostol 25 µg tablets vaginally. Induction to delivery interval, outcomes of labor, maternal adverse effects and acceptabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…12 Masood et al demonstrated that 33% women in Foley's catheter and 28% women in misoprostol group had cesarean for failed induction. 18 Agarwal et al also favors fetal distress as the main reason for cesarean in both misoprostol and Foley's catheter group. 10 Results of this study was in accordance with above studies.…”
Section: Discussionmentioning
confidence: 99%
“…12 Masood et al demonstrated that 33% women in Foley's catheter and 28% women in misoprostol group had cesarean for failed induction. 18 Agarwal et al also favors fetal distress as the main reason for cesarean in both misoprostol and Foley's catheter group. 10 Results of this study was in accordance with above studies.…”
Section: Discussionmentioning
confidence: 99%